How Green Accounting Drives Corporate Sustainability: A Mediated Moderated Model of MFCA and Resource Efficiency - Alia Rezki Amalia; Muhammad Raihan Mubaraq (West Science Social and Humanities Studies, 2026)
Corporate sustainability has become a primary focus in the global business agenda, with an increasing number of companies seeking ways to integrate environmentally responsible business practices. In this context, this study aims to investigate the influence of green accounting implementation on corporate sustainability by considering the material flow cost accounting approach, while also examining the moderating effect of resource efficiency. The sample of this study consists of manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the period 2022–2024. Data were collected by reviewing the financial reports and sustainability reports of the selected sample companies. The data analysis technique employed was path analysis using Smart Partial Least Square (SmartPLS) software. The hypothesis testing results indicate that green accounting has a positive influence on corporate sustainability. Green accounting has a positive influence on material flow cost accounting. Material flow cost accounting has a positive influence on corporate sustainability. Green accounting has a positive influence on corporate sustainability through material flow cost accounting. Furthermore, resource efficiency was found to be unable to moderate the positive influence of green accounting on corporate sustainability.